Is inclusion a valid control for ostracism?. Issue 1 (2nd January 2019) - Dvir, Maayan; Kelly, Janice R.; Williams, Kipling D
ABSTRACT: Considerable knowledge about ostracism's impact comes from research using Cyberball, an online ball-tossing game. In Cyberball, the inclusion condition is the control condition, to which ostracism is compared. The assumption is that Cyberball-inclusion is not affirming and represents an expected level of inclusion. However, without a no-inclusion control condition, it is unclear whether inclusion elevates need satisfaction, whether ostracism depresses need satisfaction, or both. We introduce Cybertree—a control condition designed to provide a similar experience to Cyberball without inclusion. Individuals playing Cybertree did not differ from included individuals in terms of feeling ostracized, level of need satisfaction, and mood. Both Cyberball inclusion and Cybertree differed significantly from ostracized individuals. We conclude that Cyberball inclusion is a reasonable control group for Cyberball ostracism but discuss research questions that may benefit from the use of Cybertree.